2017
DOI: 10.1155/2017/6209605
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Delivery according to Leisure Time Physical Activity before and during Pregnancy: A Multicenter Cohort Study of Low-Risk Women

Abstract: Objectives. To examine the association between maternal leisure time physical activity and mode of delivery. Study Design. Population-based multicentre cohort. From the Danish Dystocia Study, we included 2,435 nulliparous women, who delivered a singleton infant in cephalic presentation at term after spontaneous onset of labor in 2004-2005. We analysed mode of delivery according to self-reported physical activity at four stages, that is, the year before pregnancy and during first, second, and third trimester, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
2
12
1
3
Order By: Relevance
“…Improved physical fitness is usually observed in women who exercise during pregnancy [6] and is associated with better perinatal health outcomes [7,8]. However, while it is well-established that physical activity improves birth outcomes [9][10][11], studies looking at the relationships between objective assessments of fitness and delivery type, gestational age, duration of labour stages, birth weight and values of umbilical cord blood gas are limited. The causes of caesarean sections and how to reduce caesarean section rates are now a spotlight of research as this type of delivery has been associated with an increased risk of infection compared with vaginal deliveries, higher wound dehiscence, haemorrhage and reduced fertility [12][13][14], as well as an increased risk of allergies, type 1 diabetes or respiratory problems [15] in infants, among other complications.…”
Section: Introductionmentioning
confidence: 99%
“…Improved physical fitness is usually observed in women who exercise during pregnancy [6] and is associated with better perinatal health outcomes [7,8]. However, while it is well-established that physical activity improves birth outcomes [9][10][11], studies looking at the relationships between objective assessments of fitness and delivery type, gestational age, duration of labour stages, birth weight and values of umbilical cord blood gas are limited. The causes of caesarean sections and how to reduce caesarean section rates are now a spotlight of research as this type of delivery has been associated with an increased risk of infection compared with vaginal deliveries, higher wound dehiscence, haemorrhage and reduced fertility [12][13][14], as well as an increased risk of allergies, type 1 diabetes or respiratory problems [15] in infants, among other complications.…”
Section: Introductionmentioning
confidence: 99%
“…These differences between vaginal and caesarean deliveries might have been stronger with a larger sample size. In fact, Nielsen et al found a decrease in the rate of caesarean sections in women who had greater PA levels during the first and second trimesters of pregnancy. These results could be explained by an improvement in placental function in exercised pregnant women .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a higher rate of considering nutrition facts label in the control group may reveal a relationship between the higher rate of C-section and the lack of knowledge in nutrition, diet, and physical activity. The lack of knowledge may result in the inability to have a vaginal delivery [12].…”
Section: Resultsmentioning
confidence: 99%